Pharmacokinetic study of the novel, synthetic trioxane antimalarial compound 97-78 in rats using an LC-MS/MS method for quantification - Singh, Rajendra Pratap; Sabarinath, S; Gautam, Nagsen; Gupta, Ram Chandra; Singh, Shio Kumar (Arzneimittelforschung, 2011)
The present study has been designed to investigate the pharmacokinetic parameters of the novel trioxane antimalarial 97-78 (US Patent 6316493 Bl, 2001) in male and female rats after single oral and intravenous administration. The pharmacokinetic profile of 97-78 was investigated in the form of its completely converted metabolite 97-63 after dose administration. Quantification of metabolite 97-63 in rat plasma was achieved using a simple and rapid LC-MS/MS method. The LC-MS/MS method has been validated in terms of accuracy, precision, sensitivity and recovery for metabolite 97-63 in rat plasma. The intra- and inter-day accuracy (% bias) and precision (% RSD) values of the assay were less than 10% for metabolite 97-63. The chromatographic run time was 4.0 min and the weighted (l/x2) calibration curves were linear over the range 1.56-200 ng/ml. This method was successfully applied for analysis of pharmacokinetic study samples. Maximum plasma concentrations of 97-63 at 47 mg/kg oral administration in male and female rats were 1986.6 ng/ml and 4086.7 ng/ml at time (Tmax) 0.92 h and 0.58 h, respectively. The area under the curve (AUC0−∞), elimination half-life (t1/2 β) and mean residence time (MRT) were 4669.98 ng · h/ml, 2.8 h and 4.2 h in male and 11 786.0 ng · h/ml, 4.52 h and 4.32 h in female rats respectively. After single oral and intravenous administration of 97-78 to male and female rats significant differences were observed in pharmacokinetic parameters (AUC and t1/2 β) for metabolite 97-63.
Keywords: Antimalarial drug 97-78, pharmacokinetics; LC-MS/MS; Metabolite 97-63; 1,2,4-Trioxanes